Optimizing the net transfer capacity of a cross-border interconnector by Reactive Power Planning - Farrokhseresht, Mana; Farrokhseresht, Nakisa; Hesamzadeh, Mohammad Reza (IEEE Power & Energy Society General Meeting, 2016)
In this paper, a method for Reactive Power Planning (RPP) is proposed which ensures voltage stability in a system with cross-border electricity flows. One or more cross-border tie-lines connect the Source-area, containing cheap generation, to the Sink-area which is willing to import this cheap power. A mathematical method is used to maximize the economic benefit of the Sink-area with respect to the cost of the installed reactive compensators which maximize the Net Transfer Capacity (NTC) of the tie-lines. An analytic expression for the NTC does not exist and two methods are henceforth proposed to approximate the NTC: (1) approximation by a piecewise linear function and (2) by a polynomial obtained with statistical regression. The method is programmed in GAMS and formulated as a Mixed-Integer Non-Linear Programming problem (MINLP).